2014
DOI: 10.7771/1541-5015.1412
|View full text |Cite
|
Sign up to set email alerts
|

Using Online Digital Tools and Video to Support International Problem-Based Learning

Abstract: The goal of this study is to examine how to facilitate cross-cultural groups in problem-based learning (PBL) using online digital tools and videos. The PBL consisted of two video-based cases used to trigger student-learning issues about giving bad news to HIV-positive patients. Mixed groups of medical students from Canada and Hong Kong worked with facilitators from each country along with an expert facilitator. The study used AdobeConnect to support the international model through synchronous video interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 25 publications
(29 reference statements)
1
28
1
1
Order By: Relevance
“…The emergent themes suggest that students’ positive attitudes toward participating in the RIPPLE program stemmed in part from their motivations and expectations to enhance their own academic and personal growth, as well as to develop their intercultural awareness. Other studies [14, 15, 29] have similarly reported that undergraduate medical students welcome the opportunity to learn in intercultural environments especially when actively participating in authentic learning activities. The pre-RIPPLE survey response rate for the UNDANA students also seems to suggest that they were more motivated to volunteer to participate in RIPPLE than their UTAS counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…The emergent themes suggest that students’ positive attitudes toward participating in the RIPPLE program stemmed in part from their motivations and expectations to enhance their own academic and personal growth, as well as to develop their intercultural awareness. Other studies [14, 15, 29] have similarly reported that undergraduate medical students welcome the opportunity to learn in intercultural environments especially when actively participating in authentic learning activities. The pre-RIPPLE survey response rate for the UNDANA students also seems to suggest that they were more motivated to volunteer to participate in RIPPLE than their UTAS counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Literature on problem-based learning (PBL) has shown many benefits such as increasing content knowledge and critical thinking, communication, and collaboration skills (Lajoie et al, 2014;Sánchez & Olivares, 2011;Şendağ & Odabaşı, 2009). In most PBL studies conducted in the K-12 setting, the research participants often were gifted or regular (general) education students.…”
Section: Introductionmentioning
confidence: 99%
“…A PBL is described as an inquiry-based instructional method that facilitates students learning through collaboration and problem-solving (Barrows and Tamblyn 1986;Hmelo-Silver and Barrows 2008;Lajoie et al 2014). With the facilitators' guidance, students apply their prior knowledge, practice effective problem-solving and critically analyze the task (Hmelo-Silver 2004;Hmelo-Silver and Desimone 2013).…”
Section: Problem-based Learning (Pbl)mentioning
confidence: 99%
“…PBL supports collaborative knowledge construction and in the process learners develop skills of critical analysis, problem solving and content knowledge (Lajoie et al 2014;Hmelo-Silver 2004). Research has established that effective selfregulation leads to better learning (Azevedo 2009;Pintrich 2000;Saab, van Joolingen, and van Hout-Wolters 2012;Winne and Perry 2000;Zimmermann 2008).…”
mentioning
confidence: 99%